3-Aryl-3-(trifluoromethyl)diazirines as Versatile Photoactivated "Linker" Molecules for the Improved Covalent Modification of Graphitic and Carbon Nanotube Surfaces - Lawrence, E; Wildgoose, G; Aldous, L; Wu, Y; Warner, J; Compton, R; McNaughter, P (2011)
3-Aryl-3-(trifluoromethyl)diazirines are shown to be synthetically useful photoactivated carbene precursors that can be used as molecular "tethers" to facilitate the improved covalent surface modification of graphitic carbon and carbon nanotubes with a potentially large variety of chemical species. Proof-of-concept is demonstrated by the synthesis, as well as spectroscopic and electrochemical characterization, followed by photoactivated attachment of the organometallic diazirine derivative, 3-[3-(trifluoromethyl) diazirin-3-yl]phenyl ferrocene monocarboxylate, to the surface of vitreous carbon, and also to two different morphologies of multiwalled carbon nanotubes ("bamboo-like" and "hollow-tube", denoted as b-MWCNTs and h-MWCNTs, respectively). The latter differ only in the relative amounts of "edge-plane-like" defect sites (at the termini of the nanotubes) and "basal-plane-like" pristine sidewall regions. The facile covalent coupling of the ferrocenyl "probe" moiety to the diazirine "linker" was confirmed by UV-vis, 1H and 19F NMR spectroscopy, and cyclic voltammetry (CV). Upon exposure to UV irradiation in the presence of graphitic materials, the resulting covalent surface attachment of the ferrocenyl groups via the diazirine "linker" was characterized by Raman and X-ray photoelectron spectroscopy (XPS) and by CV experiments performed in nonaqueous electrolyte. The surface coverage of 3-[3-(trifluoromethyl)diazirin-3-yl]phenyl ferrocene monocarboxylate, analyzed from both CV and XPS experiments was found to be 7%-11% of that estimated for a complete monolayer, and was 20-fold greater than that achieved in control experiments that employed conventional covalent modification strategies to form esters between ferrocene methanol and surface carboxylate groups on the graphitic materials. The surface loading of ferrocene groups on the b-MWCNTs was found to be only ca. 60%-70% that achieved on h-MWCNTs, reflecting the ability of the functionalized carbene intermediate formed upon photolysis of the parent diazirine to insert into C=C bonds in the otherwise relatively inert sidewalls of the nanotubes. This was further confirmed by Raman spectroscopic characterization, which revealed that the h-MWCNTs experienced significantly more sidewall functionalization than the b-MWCNTs, yet still retained good electronic conduction in electrochemical experiments. The relative chemical stability of 3-aryl-3-(trifluoromethyl)diazirines, the ease with which they can be potentially be coupled to a large range of different organic, inorganic, and biological species, and the enhanced surface loading that can be achieved as a result of the reactive carbene intermediate formed during their photolysis, render diazirines highly versatile and potent "linker" molecules for the development of chemically modified materials. © 2011 American Chemical Society.